2021
DOI: 10.3390/curroncol28020138
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Patient-Reported Outcomes Following Consent for Genetic Testing Using an Oncologist- or Genetic Counselor-Mediated Model of Care

Abstract: This study compares knowledge, experience and understanding of genetic testing, and psychological outcomes among breast and ovarian cancer patients undergoing multi-gene panel testing via genetic counselor-mediated (GMT) or oncologist-mediated (OMT) testing models. A pragmatic, prospective survey of breast and ovarian cancer patients pursuing genetic testing between January 2017 and August 2019 was conducted at the Princess Margaret Cancer Centre in Toronto, Canada. A total of 120 (80 GMT; 40 OMT) individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Similar strategies have been implemented in more common malignancies, such as breast and colorectal cancer, and have increased the rates of germline testing in those conditions as well [9,18]. However, differences in the quality of pre-test counseling provided by oncology staff compared to genetic counselors have been detected [19]. In our study, an educational video was utilized to address this gap, as automation of components of pre-test counseling has been previously shown to improve patient knowledge of germline testing and feelings of empowerment [20].…”
Section: Discussionmentioning
confidence: 99%
“…Similar strategies have been implemented in more common malignancies, such as breast and colorectal cancer, and have increased the rates of germline testing in those conditions as well [9,18]. However, differences in the quality of pre-test counseling provided by oncology staff compared to genetic counselors have been detected [19]. In our study, an educational video was utilized to address this gap, as automation of components of pre-test counseling has been previously shown to improve patient knowledge of germline testing and feelings of empowerment [20].…”
Section: Discussionmentioning
confidence: 99%
“…We compared these outcomes to those of a control group receiving standard genetic care (pre-test counseling performed by a genetic counselor or clinical geneticist). So far, only four previous studies have evaluated genetic care of patients receiving mainstreamed genetic care in direct comparison to a valid control group, and for the majority with a limited number of patients in these groups [16,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown high acceptability of mainstream genetic testing approaches among EOC patients [5,6,[15][16][17][18][19][20][21]. So far, these outcomes have only been evaluated sporadically with a control group receiving pre-test genetic counseling at a genetics department [16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations